The Dynamics and Spillovers of Management Interventions: A Comment on Bianchi and Giorcelli (2022) - Gonçalo Lima; Jakob Moeller; Marco Schmandt; Christian Westheide (Institute for Replication (I4R), 2023)
Bianchi and Giorcelli (2022) study the long-term and spillover effects of a management intervention program on firm performance in the US, between 1940 and 1945. The authors find that the Training Within Industry (TWI) program led to positive effects which lasted for at least 10 years. Firm sales of treated firms increasedd by 5.3% in the first year after implementation, peaking at 21.7% after 8 years, before reducing to 16% gains after a decade. The authors claim that the program generated long-lasting changes in man- agerial practices. Finally, the program also led to positive spillover effects on the supply chain of treated firms. First, we reproduce the paper's main findings. Second, we test the ro- bustness of the results to (1) changing the main specification sample and (2) testing other difference-in-differences estimators, using the same data, pro- vided by the authors. We find that the results are robust to these changes. All point estimates in the study remain statistically significant and of similar magnitude. While the paper's finding reproduce and replicate, challenges in reproduc- ing results we encountered lead us to recommend improvements to journals' code policies.
Keywords: 330